Broadband Achromatic Sub‐Diffraction Focusing by an Amplitude‐Modulated Terahertz Metalens. Issue 21 (16th August 2020) - Zhao, Fen; Li, Ziping; Dai, Xuemei; Liao, Xiaoyu; Li, Sheng; Cao, Juncheng; Shang, Zhengguo; Zhang, Zhihai; Liang, Gaofeng; Chen, Gang; Li, Hua; Wen, Zhongquan
Abstract: Recently, there are growing interests in developing super‐resolution metalenses for applications of focusing and imaging. On one hand, various sub‐diffraction metalenses have been demonstrated; however, most of them only work at a single wavelength or multiple discrete wavelengths. On the other hand, the previously reported broadband achromatic metalenses are diffraction‐limited, or their focal spots are larger than the corresponding Abbe diffraction limit, 0.5λ/NA, where λ and NA are the lens working wavelength and numerical aperture. In the present work, an approach of realizing broadband achromatic sub‐diffraction focusing is proposed utilizing both dispersion engineering and wave front manipulating through amplitude modulation. To verify this concept, based on high‐index dielectric meta‐atoms, a broadband achromatic sub‐diffraction focusing metalens is designed with a radius of 5.11 mm, a focal length of 40.39 mm, and NA of 0.125 in the terahertz frequency range of 2.29–2.70 THz by simultaneously controlling the distributions group of the delay, frequency‐dependent phase, and amplitude transmittance. Both theoretical and experimental results demonstrate the performance of achromatic sub‐diffraction focusing within the bandwidth. The proposed approach provides a simple way to achieve broadband achromatic super‐resolution metalenses, which may have promising potentials in various applications of super‐resolution focusing and super‐resolution imaging. Abstract : There is great interest in developing super‐resolution metalenses for applications of focusing and imaging. However, it is a great challenge to achieve broadband achromatic super‐resolution performances. Here, an approach of realizing broadband achromatic sub‐diffraction focusing is proposed and verified utilizing both dispersion engineering and wave front manipulating, which may have promising potentials in super‐resolution focusing and super‐resolution imaging.